Catheter based radiofrequency ablation of renal nerves for the treatment of resistant hypertension - Markus P. Schlaich; Dagmara Hering; Murray D. Esler (Italian Journal of Medicine, 2013)
Introduction Resistant hypertension is a common and growing clinical problem characterized by the failure to attain target blood pressure levels despite adequate use of at least three antihypertensive agents. Objectives The aim of this article is to emphasize the role of novel approaches to treat resistant hypertension. Materials and methods After an excursus on the physiological role of renal nerves on kidney function, volume homeostasis and blood pressure control, this article describes the radiofrequency ablation technology to obtain kidneys denervation. Results Activation of the sympathetic nervous system plays a prominent role as a major regulator of circulatory and metabolic control. The kidneys have a particularly dense afferent sensory and efferent sympathetic innervation and are thereby strategically positioned to be origin as well as target of sympathetic activation. In this context, recent evidence suggests that a novel catheter-based approach to functionally denervate the human kidneys using radiofrequency ablation technology may provide a safe and effective treatment alternative for resistant hypertension and its adverse consequences. Conclusions Despite the availability of numerous safe and effective pharmacological therapies to treat elevated blood pressure, novel therapeutic approaches are warranted to improve the management and prognosis of patients with refractory hypertension. Several clinical trials are currently conducted and planned to further substantiate the blood pressure lowering efficacy of this novel renal denervation procedure.